Upgrading training in the Banking sector : design perspectives within the context of the German Qualifications Framework - Hackel, Monika [Verfasser] (My University, 2014)
"Despite the banking sector's high proportion of employees with higher education entrance qualifications, dual initial and advanced vocational training has been the dominant training strategy to date. But will the sector continue to withstand the general increasing trend towards academicisation? And what options are available for maintaining the attractiveness of these traditionally evolved structures for advanced vocational training in future? With reference to data on the current and future employment situation in the banking sector, the article reflects on requirements for the future design of upgrading routes for the sector. In the process, it shines a light on new parameters and opportunities presented by the introduction of the DQR." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2.4.2.4 Kredit und Versicherung; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; S 1.5.2 Berufliche Weiterbildung; G 2.4.1 Bildungs- und Berufswege; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; Bankgewerbe; Beschäftigtenstruktur; Aufstiegsfortbildung; Weiterbildungsangebot; Deutscher Qualifikationsrahmen